2016
DOI: 10.1055/s-0042-116493
|View full text |Cite
|
Sign up to set email alerts
|

Incidental (Prophylactic) Salpingectomy at Benign Gynecologic Surgery and Cesarean Section: a Survey of Practice in Austria

Abstract: l " ovarian cancer l " prophylactic salpingectomy l " incidental salpingectomy l " risk-reducing salpingectomy Schlüsselwörter l " Ovarialkarzinom l " prophylaktische Salpingektomie l " inzidentelle Salpingektomie l " risikomindernde Salpingektomie

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 28 publications
1
7
0
4
Order By: Relevance
“…In conclusion, we have previously shown that salpingectomy in lieu of BTL at the time of cesarean delivery is feasible, and this practice is on the rise both in the United States and globally. 41,48 Thus, evaluating the cost-effectiveness of this strategy is necessary. In women undergoing cesarean with permanent sterilization, opportunistic salpingectomy is almost always cost-effective, and can even be cost-saving, in comparison to BTL for ovarian cancer risk reduction.…”
Section: Commentmentioning
confidence: 99%
“…In conclusion, we have previously shown that salpingectomy in lieu of BTL at the time of cesarean delivery is feasible, and this practice is on the rise both in the United States and globally. 41,48 Thus, evaluating the cost-effectiveness of this strategy is necessary. In women undergoing cesarean with permanent sterilization, opportunistic salpingectomy is almost always cost-effective, and can even be cost-saving, in comparison to BTL for ovarian cancer risk reduction.…”
Section: Commentmentioning
confidence: 99%
“…[ 19 ] In Austria, PBS is now widely performed during benign gynecologic surgery and cesarean section. [ 20 ] We need further research to know the knowledge and practice among OBGYNs regarding this issue. Among low-risk women undergoing pelvic surgery, PBS is a cost-effective strategy for decreasing ovarian cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…In the USA, Dilley and colleagues calculated that salpingectomy at the time of hysterectomy for prevention of ovarian cancer is both cost‐effective and cost saving. Accordingly, prophylactic salpingectomy at the time of gynaecological surgery is now performed widely and routinely in many areas of the world.…”
Section: Introductionmentioning
confidence: 99%